A Comparative Study on Serum Level Concentration of Micronutrients Like Zinc, Copper and Chromium Status in Type 2 Diabetic Patients in Diabetes & Endocrinology Unit, Tikur Anbessa Specialized Hospital, Ethiopia - Mathewos Geneto,; Melaku Umeta,; Tedla Kebede,; Aklilu Azazh,; Ravi Nagphaul ,; Salahuddin Farooq Mohammed, (Journal of Pharmacy and Nutrition Sciences, 2015)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder, characterized by an absolute or relative deficiency of insulin and insulin resistance. Many studies have reported an association between diabetes and alterations in the metabolism of several micronutrients. In Ethiopia the study in the relationship between micronutrients (Zn, Cu and Cr) status and type 2 diabetes (T2DM) is scanty. The aim of this study was to assess and compare the concentration of the fasting serum zinc, copper and chromium status in T2DM and control subjects. Method: A cross-sectional comparative study, conducted on 108 human subjects divided in to two groups: 54 subjects with the diagnosis of T2DM and the other 54 subjects were grouped as the control. After demographic and anthropometric information gathered, the blood sample was collected for the biochemical analysis. Fasting serum glucose was measured by glucose oxidase methods. The serum concentration of micronutrients namely zinc, copper and chromium were determined by using atomic absorption spectrophotometer. Data were analyzed using SPSS version 16 software. Results: Compared with control groups, T2DM patients had greater BMI (p<0.001); higher WHR (p<0.001); elevated SBP (p<0.001); and higher diastolic DBP (p<0.001). Fasting serum glucose level of T2DM (196.4 ± 86.77mg/dl) was significantly higher than control (90 ± 14.39mg/dl). Mean serum levels of zinc in T2DM (0.744 ± 0.211mg/l) was significantly (p<0.003) lower than control (1.099 ± 0.502mg/l), chromium (0.679 ± 0.413 mg/l) was also significantly (p<0.0001) lower than control (1.064±0.483mg/l) and Cu (0.502±0.148mg/l) had significantly (p<0.0001) higher than control (0.340±0.137mg/l). In this study, the fasting serum glucose were found negatively correlated with serum levels of Zn (r= -0.290, p=0.033), and Cr (r=-0.012, p<0.0001) of diabetic subjects. Non-significant positive relationship was observed between concentrations of serum glucose and Cu(r = 0.438, p =0.113). Conclusion: Findings of this study indicated a lower serum zinc and chromium concentrations and higher copper status were found in type 2 diabetics of Ethiopian subjects. The study suggests that another research should be conducted in the effect of the supplementation of micronutrients on controlling of type 2 diabetic mellitus.